Illness Perception and Healing Practices among the Batek Tribe in Kuala Koh, Kelantan, Malaysia - Ramle Abdullah; Amran Ahmed; Lua Pei Lin; Aryati Ahmad; Asmawi Ibrahim; Nur Hafizah Ramle; Mohd Sukhairi Mat Rasat (2014)
The Orang Asli is one of the indigenous ethnic groups in Malaysia, with its majority residing within outskirt and rural areas. Such a settlement distribution pattern largely influences their culture including the aspects of medicinal practices. Although they are exposed to modernisation elements by the Malaysian government, part of the culture and traditional lifestyles especially in the aspects of illnesses healing are still largely practiced. Studies were carried out towards the Batek tribe in Kuala Koh, Kelantan to examine two (2) questions; (i) what are their perceptions towards the causes of illnesses? And (ii) what are the approaches taken in treating illnesses? During the research, participation observation and interview techniques were applied in the data gathering process. Documents produced by previous researchers were also analyzed as a basis for focus discussions related to the issues at hand. The results showed that the Batek tribe believes that sickness suffered by individuals stems from two (2) factors. First, factors related to spiritual elements such as harassment by the supernatural powers and faint-heartedness. Second, physical factors related to changes in natural phenomenon and human negligence in exploiting natural resources. Based on these beliefs the Batek tribe possesses two approaches in treating illnesses. First, through means of faith-healing, for sickness believed to originate from spiritual factors. Second, the application of herbs obtained from forests surrounding their settlements.